Penerapan Supervisi Akademis dalam Meningkatkan Kemampuan Guru Menyusun Asesmen - Gushardiyati, Teti (Universitas Suryakanca, 2024)
This article will explain the skills of class teachers in compiling assessment instruments. The method used is descriptive comparative with a qualitative approach in the form of classroom action research consisting of two cycles. The research was carried out after looking at the data from the supervision of the assessment tools prepared and owned by the class teachers at SD Negeri Ibu Dewi 1 Cianjur which turned out to be still at a deficient and basic level. The steps taken by all teachers include the activities (1) compiling question indicators, (2) developing questions according to the question indicators, (3) preparing questions according to cognitive level. (4) compose written questions in accordance with the rules for preparing questions, and (5) create a scoring rubric for essay questions. The results of the research showed that there was an increase in the ability of teachers in compiling assessment tools from pre-cycle to cycle I by 12.99% (from the poor category to the good category) and from cycle I to cycle II by 13.51% (from the good category to the very good category). Good).Keywords: assessment; teacher ability; supervisionAbstrak:Artikel ini akan memaparkan keterampilan guru-guru kelas dalam menyusun instrumen penilaian. Metode yang digunakan adalah deskriptif komparatif dengan pendekatan kualitatif dalam bentuk penelitian tindakan kelas yang terdiri atas dua siklus. Penelitian dilaksanakan setelah melihat data hasil supervisi terhadap perangkat penilaian yang disusun dan dimiliki oleh guru-guru kelas SD Negeri Ibu Dewi 1 Cianjur ternyata masih berada pada tingkat kurang dan apa adanya. Adapun langkah yang dilakukan oleh semua guru meliputi kegiatan-kegiatan (1) menyusun indikator soal, (2) mengembangkan soal sesuai indikator soal, (3) menyusun soal sesuai dengan level kognitif. (4) menyusun soal tertulis sesuai dengan kaidah penyusunan soal, dan (5) membuat rubrik penskoran pada soal uraian. Hasil penelitian menunjukkan terjadi peningkatan kemampuan guru- guru dalam menyusun perangkat asesmen dari prasiklus ke siklus I sebesar 12,99% (dari kategori kurang ke kategori baik) dan sari siklus I ke siklus II sebesar 13,51% (dari kategori baik ke kategori sangat baik).Katakunci: asesmen; kemampuan guru; supervisi